Tracings from the Acts of the Apostles or thirty yoears of Christian work - Stuart, Clarence Esme, 1823-1903 (London, UK Marlborough)
Includes index.
Brethren writer. Donated by the late Miss M. Kemp.
Keywords: Bible. N.T. Acts -- outlines